(untitled) (Jóvenes en la Ciencia, 2026)
In Mexico, a significant part of the food produced is lost before reaching consumers due to failures in the cold chain. This situation strongly affects highly perishable crops such as asparagus, which requires rapid cooling to preserve its quality. This article clearly explains how the cold chain works in Mexican agriculture, why it is essential for handling asparagus, and what challenges regions like Guanajuato face in maintaining it. The aim is to highlight the importance of proper cooling and storage practices to reduce losses, maintain product quality, and support the competitiveness of agricultural production.